2011
DOI: 10.1039/c1cc10491h
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bonding—a key step in charge recombination of the dye-sensitized solar cell

Abstract: The halogen bonding between [Ru(dcbpy)(2)(SCN)(2)] dye and I(2) molecule has been studied. The ruthenium complex forms a stable [Ru(dcbpy)(2)(SCN)(2)]···I(2)·4(CH(3)OH) adduct via S···I interaction between the thiocyanate ligand and the I(2) molecule. The adduct can be seen as a model for one of the key intermediates in the regeneration cycle of the oxidized dye by the I(-)/I(3)(-) electrolyte in dye sensitized solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 35 publications
(40 reference statements)
3
83
0
Order By: Relevance
“…25,26 Also, adduct formation with iodine has been studied by X-ray diffraction. 27 These studies reveal interactions between iodide or iodine and the sulfur atom of the isothiocyanate ligand as well as ligand-exchange reactions between I − and SCN − moieties. Interaction of iodide with bipyridyl rings of the dye is also proposed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…25,26 Also, adduct formation with iodine has been studied by X-ray diffraction. 27 These studies reveal interactions between iodide or iodine and the sulfur atom of the isothiocyanate ligand as well as ligand-exchange reactions between I − and SCN − moieties. Interaction of iodide with bipyridyl rings of the dye is also proposed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this structure, reported by M. Haukka et al [76], one I 2 molecule bridges two sulfur atoms of two isothiocyanate units at two different metal complexes (I1⋅⋅⋅S2 2.954 Å and I4⋅⋅⋅S1 3.531 Å, 22 and 7% van der Waals radii reduction, respectively) ( Fig. 8.16, right).…”
Section: Xb Acceptors From The16thmentioning
confidence: 99%
“…Light induced photovoltage measurements [8] and impedance studies [9,10] on dye series which have similar physical barriers to recombination have also shown that the rate of recombination across the TiO 2 /electrolyte interface is affected by the dye structure. [11] Binding between I 2 and the bpy ligands is weak, [8] and growth of a crystal of an N3-I 2 adduct [12] showed that I 2 binds to the sulfur atoms of the -NCS ligands. Further studies have shown that I 2 can also bind to substituent groups such as NH 2 on ancillary ligands -which results in poorer cell efficiencies.…”
Section: Introductionmentioning
confidence: 98%